A review of solar drying architecture: Direct, indirect and mixed-mode solar dryer - Permana Andi Paristiawan; Ihwan Ghazali; Dwi Aryanti; Budiarjono Budiarjono; Ayu Amanah; Muhammad Idris; Dhany Hermansyah; Esam Abu Baker Ali (Jurnal POLIMESIN, 2022)
Solar energy is available in abundance. It is considered an effective energy source for drying agricultural products. Although it is affordable, open sun drying suffers from both qualitative and quantitative issues caused by unexpected environmental conditions (rain, dust), animals (insects, birds, rodents), and over-or under-drying. Therefore, it is important to introduce a better drying technology to preserve solar energy without deteriorating the quality of the drying product. For that reason, solar dryers have been developed to produce higher drying temperatures and lower relative humidity that will eventually lead to superior drying rates and reduced final moisture contents compared to the conventional open sun drying method. Therefore, not only does the solar dryer meet the requirements of agricultural products, but it also saves energy, time, and money.